2013
DOI: 10.1080/10508406.2012.729767
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Systems of Practice: A Multidimensional Analysis of Math and Science Undergraduate Course Planning and Classroom Teaching

Abstract: Descriptions of faculty practice that illuminate nuances of how course planning and classroom instruction occur in specific contexts are important to inform pedagogical interventions. The study reported in this article draws on systems-of-practice theory to focus on the dynamic interplay among actors, artifacts, and tasks that constrains activities such as course planning and constitutes other activities, such as classroom instruction. This qualitative case study of faculty teaching in math and science discipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 60 publications
3
83
0
1
Order By: Relevance
“…Within the last three years in LA, SNA has been shown to be an effective tool to explore the relationships of learners in online discussion forum [29], as well as in face-to-face interactions, tracked for instance in eye tracking movements [32]. However, none has looked at the LD from a social network perspective, identifying connections between learning activities using 'big data'.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the last three years in LA, SNA has been shown to be an effective tool to explore the relationships of learners in online discussion forum [29], as well as in face-to-face interactions, tracked for instance in eye tracking movements [32]. However, none has looked at the LD from a social network perspective, identifying connections between learning activities using 'big data'.…”
Section: Discussionmentioning
confidence: 99%
“…However, none has looked at the LD from a social network perspective, identifying connections between learning activities using 'big data'. Hora, Ferrare [29] suggested that teaching practice should be best viewed as situated in and distributed among features of particular settings. According to the systems-of-practice theory by Halverson [33], local practices are informed, constrained, and constituted by the dynamic interplay of artifact and tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral observation of the non-lab portion of the course was conducted as a course evaluation measure in 2014 and 2015 using the TDOP -or Teaching Dimensions Observation Protocol 26 . Using the TDOP, the total class period was divided into a series of five-minute segments.…”
Section: Classroom Evaluation Methodsmentioning
confidence: 99%